Effectiveness of School Resources Management in Improving The Quality of Education - Agustina Muliati; Winda Sihotang; Rini Ade Octaviany; Darwin (East Asian Journal of Multidisciplinary Research, 2022)
This study aims to describe the effectiveness of school resource management in improving the quality of education. The quality of education includes a description of the ability of education in schools in accordance with the standards and objectives to be achieved. This study uses a descriptive type of research and a qualitative approach. The results of the study indicate that the quality of education is the ability of the education system to increase the added value of input factors in order to produce quality outputs. Implementation of School-Based Management (SBM) requires the involvement of all resources who have the ability to empower to be empowered by schools on an ongoing basis by applying an integrated problem-solving approach to management.